Coherent Coupling Between a Superconducting Qubit and a Spin Ensemble in a Hybrid Quantum System for Microwave-to-Optical Transduction - Raul Gomez; Thiago Rocha; Luis Santos (Yayasan Adra Karima Hubbi, 2025)
The coupling of superconducting qubits with spin ensembles has emerged as a promising solution to bridge the microwave-optical frequency gap in hybrid quantum systems. These systems are crucial for advancing quantum communication, quantum networks, and integrated quantum technologies. However, achieving coherent coupling between these two platforms remains a significant challenge due to the differences in their operational frequency regimes and their susceptibility to decoherence. This research aims to explore the coherent coupling between a superconducting qubit and a spin ensemble, specifically focusing on its potential for efficient microwave-to-optical transduction. The primary objective of this study is to develop a hybrid quantum system that enables the transfer of quantum information between microwave and optical domains with minimal loss of coherence. Experimental and theoretical approaches were used, involving superconducting qubits and nitrogen-vacancy (NV) centers in diamonds as the spin ensemble. The results demonstrate that the coupling mechanism is efficient, achieving high transduction efficiencies and long coherence times, particularly at optimized coupling strengths. These findings suggest that the hybrid system can be used for scalable quantum communication systems, facilitating quantum information transfer across different frequency domains. In conclusion, this study provides a robust method for microwave-to-optical transduction, opening new avenues for quantum network development and hybrid quantum technologies.